Hemodynamic assessment of intracranial atherosclerotic stenosis: comparison between invasive non-hyperemic pressure ratio and angiography-derived quantitative flow ratio - Wang, Xiaohui; Bian, Yang; Zhang, Rongju; Zhu, Haojing; Yang, Junjie; Wang, Ruiling; Liu, Xinfeng; Lv, Bin; Cao, Xiangyu; Dai, Wei; Sun, Zhibin; Jing, Jing; et al. (Frontiers in Neurology, 2024)
ObjectivesTo evaluate the diagnostic accuracy of the quantitative flow ratio (QFR) for hemodynamic exploration of intracranial atherosclerotic stenosis, using the invasive cerebrovascular pressure ratio (CVPR) and resting full-cycle ratio (RFR) as reference standards.Materials and methodsPatients with symptomatic unifocal intracranial atherosclerotic stenosis were included. The CVPR was defined as the ratio of the proximal and distal pressures. All patients underwent angioplasty under general anesthesia. The QFR was calculated based on digital subtraction angiography. Using the CVPR as a reference, we compared its correlation with the QFR across different degrees and locations of stenosis.ResultsThe CVPR and QFR were measured in 34 vessels of 32 patients. The QFR demonstrated a high correlation and excellent agreement(r = 0.8227, p < 0.001) with the CVPR in distal stenosis before intervention. In the subgroup with diameter stenosis >80%, the QFR showed a high correlation (r = 0.8812, p < 0.001) with the CVPR. In the anterior circulation subgroup, the QFR showed an excellent correlation (r = 0.9066, p < 0.001) with the CVPR. In the posterior circulation subgroup, the QFR showed a high correlation with the CVPR (r = 0.7706, p < 0.001). Diameter stenosis rates showed a moderate negative correlation with the CVPR.ConclusionThere was a strong correlation between the QFR and wire-based CVPR, especially for anterior circulation lesions before intervention. The QFR may serve as a predictive factor for evaluating hemodynamic changes in intracranial atherosclerotic stenosis.